Origin of Parisian Laws and Regulations in India: “Fons et origo of Zoroastrianism” - Shyamantak Misra1 , Prafulla Chandra Mishra2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present article is elucidation of Parsi’s and their personal laws to make it a less confused and more comprehensible study matter. The title “Fons et origo of Zoroastrianism” means the source or the origin of Zoroastrianism. Those who believed that there’s only one Supreme God namely “Ahura Mazda” are known as Zoroastrians. The researcher has discussed the status of Parsis from its inception till date. This piece of work starts with a detailed study of their origin, simplifying their upbringing and tracing their movements and further stressing on the enactment & application of their laws in India. This piece of literature, emphasizing on the origin of the Zoroastrians further focuses on the legal provisions relating to Parsi marriages, divorce and maintenance as well. In Toto it’s a compilation of the most needed information and majorly required provisos relating to Parsis.